Credit rationing at the firm level: Some microeconometric evidence - Peter Winker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
Over the last decade credit rationing has been regarded increasingly as the outcome of asymmetric Information. Profit maximization of the banks might lead to interest rates lower than the market equilibrium rate. Administering loans at a higher interest rate to the rationed customers will decrease the expected return due to adverse selection and adverse incentive effects. This paper deals with the effects of age and business relations of firms on the degree of informational asymmetry between banks and firms. The resulting impact on the probability of rationing on the loan market is also studied. The main contribution of this paper is a direct test of the resulting hypotheses with data at the firm level. Both, the influence of the age of firms and a measure of informational asymmetry on the probability of be-ing rationed on the loan market is estimated. The estimation is based on microdata of the IFO Institute for economic research, Munich.
Keywords: 330; Kreditrationierung; Unternehmenserfolg; Adverse Selektion; Mikroökonometrie; Deutschland; Theorie